1998
DOI: 10.1103/physrevlett.80.552
|View full text |Cite
|
Sign up to set email alerts
|

Fast Decay of Adatom Islands and Mounds on Cu(111): A New Effective Channel for Interlayer Mass Transport

Abstract: We report on the observation of a new and very effective mechanism of interlayer mass transport which bypasses the Schwoebel-Ehrlich barrier for the diffusion of atoms over step edges. The channel for a rapid mass transport opens when a two-dimensional island engaged in a random walk on a surface touches the boundary of a descending step. The decay rate of the island then increases by about 2 orders of magnitude. Even entire mounds can disappear in a very short time due to ledge contact events caused by equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 24 publications
6
56
1
Order By: Relevance
“…The wiggles are therefore presumably caused by the random walk of the top layer island and the changing environment of the lower island. The acceleration of the decay of top layer islands as well as the constant TW in the late stages of the decay has been shown previously [18]. It was speculated that the increased decay rate of the top layer island may be caused by the formation of microscopic contacts between the island edges due to thermal edge fluctuations and the stochastic motion of the islands.…”
Section: Institut F üR Grenzflächenforschung Und Vakuumphysik Forschmentioning
confidence: 93%
See 1 more Smart Citation
“…The wiggles are therefore presumably caused by the random walk of the top layer island and the changing environment of the lower island. The acceleration of the decay of top layer islands as well as the constant TW in the late stages of the decay has been shown previously [18]. It was speculated that the increased decay rate of the top layer island may be caused by the formation of microscopic contacts between the island edges due to thermal edge fluctuations and the stochastic motion of the islands.…”
Section: Institut F üR Grenzflächenforschung Und Vakuumphysik Forschmentioning
confidence: 93%
“…1(a) would also match the experiment if a more moderate reduction of the ES barrier had been assumed. However, the rapid decay occasionally observed when the top layer islands accidentally comes very close to the boundary of the lower island [18] requires that the ES barrier vanishes more or less completely. We point out that the data cannot be described by assuming an enlarged diffusion constant on small terraces since the activation energy for diffusion is already small (about 0.05 eV [23,24]).…”
Section: Institut F üR Grenzflächenforschung Und Vakuumphysik Forschmentioning
confidence: 99%
“…More recently, Giesen et al observed that the rates of Cu island decay on Cu(111) greatly increase when the separation distance, d, between island-and terrace-step edges is smaller than a critical value w c ≈ 14Å [10,11]. The effect was attributed to ES barriers becoming vanishingly small for d < w c , in accordance with theoretical models, which showed that quantum confinement of electronic surface states in metals occurs for terrace widths < w c = λ F / √ 2, where λ F is the Fermi-electron wavelength [12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely used model systems for such investigations is the decay of two-dimensional ͑2D͒ metal islands on metal substrates. [2][3][4][5][6][7][8][9][10][11] The thermal decay of such islands was found to reduce the island area with time t proportional to (t 0 Ϫt) 2␤ , where t 0 is the time at which the island is fully dissolved. 12 The value of the exponent ␤ is a signature of the dominant microscopic mechanism governing the rate of decay.…”
mentioning
confidence: 99%